Pengaruh Kualitas Produk Terhadap Kepuasan Pelanggan Daviena Skincare Di Zahra Beauty Surabaya - Alvin Julian Herlambang (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This research wants to find out further "The Influence of Product Quality on Customer Satisfaction" according to the title raised The Effect of Product Quality on Customer Satisfaction Daviena Skincare at Zahra Beauty Surabaya. The population in this study were consumers from Davienaa Skincare at Zahra Beauty Surabaya. In this study using a sample of 60 consumer respondents from Daviena Skincare at Zahra Beauty Surabaya, using SPSS and linear analysis can prove that Product Quality (X1) affects Customer Satisfaction (Y1),